Characterization of lncRNA Profiles of Plasma-Derived Exosomes From Type 1 Diabetes Mellitus - Pang, Haipeng; Fan, Wenqi; Shi, Xiajie; Li, Jiaqi; Wang, Yimeng; Luo, Shuoming; Lin, Jian; Huang, Gan; Li, Xia; Xie, Zhiguo; Zhou, Zhiguang (Frontiers in Endocrinology, 2022)
Backgrounds: Exosomes contain several types of transcripts, including long non-coding RNAs (lncRNAs), and have been shown to exert important effects in human diseases. However, the roles of exosomal lncRNAs in type 1 diabetes mellitus (T1DM) have not been well investigated. In the present study, we characterized the plasma-derived exosomal lncRNAs expression profiles of T1DM and predict their potential function in the pathogenesis of T1DM. Material and Methods: Exosomal lncRNA expression profiles were detected by Illumina Hiseq platform. Bioinformatics analysis approaches were carried out to explore the potential biological function of differentially expressed lncRNAs. Results: A total of 162 differentially expressed exosomal lncRNAs were identified in T1DM patients compared with control subjects, among which 77 up-regulated and 85 down-regulated. Gene Ontology (GO) analysis enriched terms such as activation of phospholipase D activity, neuronal cell body membrane, and calcium sensitive guanylate cyclase activator activity for cis-acting genes of lncRNAs, and metal ion binding for trans-acting genes. The most enriched Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways for the lncRNAs were associated with oxidative phosphorylation and Parkinson’s disease for cis-acting genes, and pathways in cancer as well as focal adhesion for trans-acting genes. Conclusions: This study characterized the lncRNA profiles of plasma-derived exosomes from T1DM for the first time and these results highlighted the potential role of exosomal lncRNAs in T1DM pathogenesis. A better understanding of exosomal lncRNA profiling will provide novel insights into its molecular mechanisms.